Updated Autopoiesic Leadership Model (Journal of Universal Excellence, 2026)
Research Question (RQ): Which variables are still improving and complementing the autopoiesic leadership model?Purpose: The research aims to improve the model with a slightly modified basic variable and complement the model with five new variables.Method: The goals of the research were achieved through the method of analysing articles and, in particular, questionnaires. By triangulating or combining different research theories within the research problem, we followed various, even contradictory, theoretical assumptions. In this way, we gained a comprehensive view of the study area.Results: In the existing model, we replaced one variable, emotional sensitivity, with sensory sharpness, while the other two variables, goal orientation and flexibility, remained unchanged. We added five new variables to the model, namely: communication skills, including posing questions, feedback and empowerment, and two variables: good impression and continual learning. These variables greatly increase the quality of the model due to the greater range of key elements. For this range of variables, we prepared a questionnaire.Organization: The results of the survey with the completed model of autopoiesic leadership provide the organisation with important information about a good leader, thus influencing the selection of the best personnel.Society: The model of autopoiesic leadership is primarily used as a self-guide, thus transforming a person. In the future, such a person can also successfully lead the team and organisation. In this way, we are building a new culture of relationships that have a key influence on society, social responsibility, and thus the whole environment.Originality: We cannot find the model of autopoiesic leadership in the world literature about management. In this way, we introduce a new dimension of the research area, which can be improved with new research activities.Limitations/Future Research: The study was limited to theoretical research. In addition, we propose other research methods for further improvement of the study model.
Keywords: autopoiesic model; autopoiesic leader; goal orientation; sensory sharpness; flexibility; triangulation of theories